2016
DOI: 10.1016/j.gerinurse.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral moisturizing jelly as a saliva substitute for the relief of xerostomia in elderly patients with hypertension and diabetes mellitus

Abstract: Dry mouth is common in elderly patients. However, the use of saliva substitute has been limited due to its inedibility. This study investigated the efficacy of oral moisturizing jelly (OMJ), a novel edible saliva substitute. A pre-post design was conducted in 118 elderly patients diagnosed with hypertension and/or diabetes mellitus. After using OMJ, signs and symptoms of dry mouth were compared with baseline data. The properties of saliva were compared between the OMJ use and non-use periods. The use of OMJ fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…Exclusion criteria included patients with mucositis grade ≥1 or with oral infection, such as candidiasis. The subjects were considered xerostomic when subjective dry mouth scores were ≥3 according to our previous study (Dalodom et al, ) and as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria included patients with mucositis grade ≥1 or with oral infection, such as candidiasis. The subjects were considered xerostomic when subjective dry mouth scores were ≥3 according to our previous study (Dalodom et al, ) and as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective dry mouth scores were obtained by interviewing the subjects according to a validated questionnaire used previously by our group (Dalodom et al, ). Briefly, the subjects were asked by one researcher to grade their problems from a scale of 0–10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product can be swallowed from oral cavity through oropharynx which resembles natural saliva. A previous study in xerostomic elderly patients with hypertension and diabetes mellitus showed that continuous intake of OMJ for 4 weeks significantly reduced signs and symptoms of dry mouth, and achieved more than 80% satisfaction [13]. Recently, DIF have produced a new version of OMJ.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly also undergo aging processes which can be aggravated by chronic diseases, such as cardio‐ and cerebrovascular, diabetes, oral cancer, osteoporosis, as well as Parkinson's and Alzheimer's disease that are common in this age group . In terms of oral diseases, this group of patients may have an increased risk of developing cervical caries, periodontitis, xerostomia, and oral candidiasis …”
Section: Introductionmentioning
confidence: 99%